A System-Independent Derivation of Preferential Attachment from the Principle of Least Effort - François Xavier Machu; Ru Julie Wang; Jean Louis Cheng; Jeremy Cocks; Qiuping Alexandre Wang (Entropy, 2023)
Preferential attachment (PA) is a widely observed behavior in many living systems and has been used in modeling many networks. The aim of this work is to show that the mechanism of PA is a consequence of the fundamental principle of least effort. We derive PA directly from this principle in maximizing an efficiency function. This approach not only allows a better understanding of the different PA mechanisms already reported but also naturally extends these mechanisms with a non-power law probability of attachment. The possibility of using the efficiency function as a general measure of attachment efficiency is also investigated.